The optimization of spectral analysis for signal harmonics. - Ta-Peng Tsao (IEEE Transactions on power delivery)
FFT has been applied to technologies of spectrum analysis widely. However, since the signal sampling is at random, and FFT suffers specific restrictions, some defects inevitably occur, which means that harmonic parameters do not show on the spectrum exactly. These defects result from frequency scales not matching signal characteristics. This paper discusses the optimization of spectrum analysis for signal harmonics. By means of scale fine-tuning, the frequency scales will match the signal characteristics. The method eliminates both of the picket-fence effect and the leakage effect; it makes the harmonic parameters show on the spectrum more accurately. This paper takes reasonable and practical evaluations to verify the theory